Design and Development of 5G MIMO Antenna with Enhanced Isolation - Naidu , G. Ajay Bhaskar; Reddy , Y. Avinash; Chowdary , C. H. Naveen (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
In this paper, MIMO 2-port, 2-element antenna for 5G applications is presented. MIMO innovation utilizes multipath to accomplish higher information rates all the while expanding unwavering quality and range without utilizing additional transmission capacity, along these lines improving unearthly efficiency to manage the need of high information rates for different administrations. This monopole antenna structure consists of a two-rectangular patch of the same shapes. Each antenna has a feeding plate connected at the centre of the patch antenna for enhancing isolation the etching of rectangular slots on the ground plane in between the two patches along with a thick and sheet of the substrate just below at the centre of the patch. Maximum isolation achieved among the ports is less than -30db. envelope correlation coefficient is below 0.10 in bands of interest. The minimum frequency range covered by the four ports of this antenna is from around 3.0 to 4.0 GHz, thus covering the expected future 5G band (3300–3700 MHz). Recently in India, the 3G service provider Reliance has started using the MIMO technology, providing the data rate at a speed of 28 Mbps. The recent researchers of MIMO technology have mainly focused on signal processing, channel modeling and coding aspects rather than the antenna design issues.